The Impact of Interpersonal Style and Interpersonal Complementarity on the Therapeutic Alliance Between Therapists and Offenders in Sex Offender Treatment. (March 2017) - Watson, Rachael; Daffern, Michael; Thomas, Stuart
Therapist and treatment process variables affect the effectiveness of offender rehabilitation programs. This study examined the influence of therapists' and offenders' interpersonal styles (IPSs) and interpersonal complementarity on therapeutic alliance (TA). Seventy-five sex offenders and their therapists evaluated each other's IPSs and the TA after 3 weeks of treatment. Offenders evaluated the TA more positively than therapists. Regarding the impact of IPS, therapist affiliation was positively correlated and therapist control was negatively correlated with offenders' ratings of the TA; in other words, offenders evaluated the TA more strongly when therapists were perceived as affiliative, and weaker when therapists were viewed as controlling. Offender affiliation was positively correlated with therapists' ratings of TA; in other words, therapists evaluated the TA more strongly when offenders were viewed as more affiliative; perceptions of offender control were unrelated to offenders' ratings of TA. Complementarity in IPS between offenders and therapists did not affect TA.